§ 2.

               23.
f(x)   h(x).

23.01.

f(x) = (32)2×(2+1)×(+1)2,

 

h(x) = (4 1) × (2 2);

23.02.

f(x)=(+1)3×(1)2×(2+1),

 

h(x)=(+1)2×(1)4×(3)×(2+1);

23.03.

f(x)=(1)3×(+1)2×(2+1),

 

h(x) =2 ( + 1)× ( 1)2× (2 + 3);

23.04.

f(x)=(2)×(24)×(38),

 

h(x)=(+1)2×(2+2+4)2×(2);

 

23.05.

f(x)=(3+8)(24)(2+2+1),

 

h(x) = ( + 2)2 × (2 4 + 4);

23.06.

f(x)=(22x+1)(3+1)(21),

 

h(x)=(1)2(2+2+1)(x2 x + 1);

23.07.

f(x)=(2x2)(2 1)(2 4),

 

h(x) = (3 1) × ( + 2)2 × ( x + 1);

23.08.

f(x)=(2+x2)(3+ 1)(2 1)

 

h(x)=(1)2 ( + 2)2(x2 + 1);

23.09.

f(x)=(364)(+4)2(216),

 

h(x)=(2+4+16)2( + 4)( 4)2;

23.10.

f(x)=(2+8x+16)(3 64)(2 16),

 

h(x)=( +4)3(2+4+16)2( 4);

23.11.

f(x)=(2+2)(416)(24x +4),

 

h(x)=(24)3(3+8)2 (2 + 2);

23.12.

f(x)=(3+2)(2+4x+4)(2 4),

 

h(x) = (4 16)2 × (2 2);

23.13.

f(x)=(327)(29)( + 3),

 

h(x)=(2+4+3) ( 3)(2 + 3 + 9)2;

23.14.

f(x)=(3+27)(29)( 3),

 

h(x)=(24+3)(3)2(2+1);

23.15.

f(x)=(2+6x+9)(2+1)(29),

 

h(x)=(327)(2+1)(26)2;

23.16.

f(x)=(3+1)(22+1)(21),

 

h(x)=(2+1)(1) 2 (2 + 2 + 1);

23.17.

f(x)=(33)2(216)(3 + 8),

 

h(x)=(33)(24+4)(2 2 + 4)2;

23.18.

f(x)=(2x12)(29)(2 16),

 

h(x)=(2+2)( 3)( 4)3;

23.19.

f(x)=(2+x12)(29)(216),

 

h(x)=(3)2(+3)2(2 6 + 9);

23.20.

f(x)=(2+8x+16)(2+2)(3 64),

 

h(x)=(4)2(2+4+16)2( + 4);

23.21.

f(x)=(28x+16)(2+2)2(3+ 64),

 

h(x)=(24+16)2(24)( 4);

23.22.

f(x) = (2 x 6)×( 3)2× ( + 2) × (2+ 6)2,
h(x) = (2 9) × (2 4) × (2 + 6);

23.23.

f(x)=(2+x6)(29)(24),

 

h(x) = (2 6)(2 + 1)( + 2);

23.24.

f(x)=(3125)(225)(2 + 6 + 5),

 

h(x)=(21)(2+10+25)(2+1);

23.25.

f(x)=(3+125)(225)(26+5),

 

h(x)=(21)(210+25)(2+2);

23.26.

f(x)=(4+4)(24)(38)(2+2+4),

 

h(x)=(24+4)(2+4)2(2+2+4);

23.27.
f(x) = (2 + 4)2× (2 4) × (3+ 8) × (2 2x + 4),
h(x) = (2 + 4 + 4) × (2 + 4) × (2 2 + 4);

23.28.

f(x) = 2(2 7x + 6)×(2 1)× ( 6) × (2 + 1),
h(x) = (3 1) × (2 + 1) × (2 2 + 1) × ( 6);

23.29.

f(x) = (2 + 7x + 6)×(2 1)× ( + 6) × (2 36),
h(x) = (2 + 12 + 36) × (2 + 2 + 1) × (2 + 1);

23.30.

f(x)=(3216)(236)(2+5),

 

h(x)=(2+5)(2+12+36)(2+6+36)2;

23.31.

f(x)=(3+216)(236)(2+5),

 

h(x)=(2+5)(212+36)(26+36)

23.32.

f(x)=(24x+3)(327)(21),

 

hx)=(29)(2+1)(2+3+9)2;

23.33.

f(x)=(2+4x+3)(3+27)(21),

 

h(x)=(29)(2 +3)(2 3+9)2(+1);

23.34.

f(x)=(23)(2+3)(3+1),

 

h(x)=(23)(481)(2+1);

23.35.

f(x)=(2+3)2(23)(31),

 

h(x)=(2+3)(481)(2++1)2;

23.36.

f(x)=(38)(24)(2+2),

 

h(x)=(2+2+4)2(24+4)(2+3).

 

\..\

                              Copyright © 2008-2009 ..   . .